Genetic heterogeneity within individual bovine rotavirus isolates. - Sabara, M (1982)
The genomic RNA patterns of six different bovine rotavirus isolates were analyzed on high-percentage polyacrylamide gels (12.5, 13.6, and 17.5%). In contrast to the RNA patterns exhibited by conventional gel systems, those on the high-percentage gels showed an improvement in segment resolution which consequently aided in the detection of extensive band splitting in these patterns. The ability to clone out various electrophoretically distinct virus subpopulations from each of the six isolates provided an explanation for the band splitting detected by the high-resolution gels. The significance of the coexistence of genetically distinct rotavirus populations within a single host is discussed.